Movement of European freshwater mussels under simulated dewatering conditions - Ana Matos; Manuel Lopes-Lima; Paulo Castro; Luigi Fraccarollo; Janusz Golski; Sandra Kaźmierczak; Vanessa Modesto; Martin Österling; Sebastiano Piccolroaz; Ashkan Pilbala; Vincent Prié; Nicoletta Riccardi; et al. (Hydrobiologia, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

First record of Phyllorhiza punctata von Lendenfeld, 1884 (Cnidaria: Rhizostomeae) in Portuguese waters: implications for regional marine ecosystems - Antonina dos Santos; Alexandra D. Silva; Pedro F. Silva; Ana Matos; Elsa Froufe (Marine Biodiversity, 2026)

Multi-tissue transcriptome of Brycon amazonicus (Spix & Agassiz, 1829): insights into lipid metabolism in an Amazonian fish - Renato Barbosa Ferraz; Elsa Froufe; L. Filipe C. Castro; Manuel Nande; Karine Vasconcelos Costa; Raimundo de Jesus Tavares Diniz Neto; Óscar Monroig; André Gomes-dos-Santos (Marine Genomics, 2025)

Review of the globally invasive freshwater mussels in the genus Sinanodonta Modell, 1945 - Karel Douda; Alexandra Zieritz; Barbora Vodáková; Maria Urbańska; Ivan N. Bolotov; Jana Marková; Elsa Froufe; Arthur E. Bogan; Manuel Lopes-Lima (Hydrobiologia, 2025)
In this review, we synthesize the current knowledge of the biology, ecology, and impact of Sinanodonta freshwater mussels (Bivalvia, Unionidae), native to East Asia, that have successfully invaded Europe, Central America, North Africa, and several Asian regions. The main introduction pathways of Sinanodonta were reconstructed based on DNA sequence data and distribution records. We show that invasive lineages of Sinanodonta belong to three species, namely, S. woodiana s. str. (“temperate invasive” lineage), S. pacifica (“tropical invasive” lineage), and S. lauta . Their generalist fish-dispersed larvae, short life span, high fecundity, use by humans for multiple purposes, and ability to establish populations in anthropogenically disturbed conditions were identified as crucial traits driving their invasions. Information on the consequences is scarcer, but Sinanodonta can impact native species through larval parasitism, host fish/food competition, and parasite transmission. In addition, ecosystem effects through their filtration—biodeposition—excretion activity and the occurrence of massive die-offs were detected. Ecosystem services and disservices have not yet been quantified, even at local scales, and management methods in the invasive range are understudied. A better understanding of Sinanodonta ecology, impacts, and management options is urgently needed to make informed decisions and set realistic and impactful restoration goals.

A multi-tissue de novo transcriptome assembly and relative gene expression of the vulnerable freshwater salmonid Thymallus ligericus - Giulia Secci-Petretto; Steven Weiss; André Gomes-dos-Santos; Henri Persat; André M. Machado; Inês Vasconcelos; L. Filipe C. Castro; Elsa Froufe (Genetica, 2024)
Freshwater ecosystems are among the most endangered ecosystems worldwide. While numerous taxa are on the verge of extinction as a result of global changes and direct or indirect anthropogenic activity, genomic and transcriptomic resources represent a key tool for comprehending species' adaptability and serve as the foundation for conservation initiatives. The Loire grayling, Thymallus ligericus , is a freshwater European salmonid endemic to the upper Loire River basin. The species is comprised of fragmented populations that are dispersed over a small area and it has been identified as a vulnerable species. Here, we provide a multi-tissue de novo transcriptome assembly of T. ligericus . The completeness and integrity of the transcriptome were assessed before and after redundancy removal with lineage-specific libraries from Eukaryota, Metazoa, Vertebrata, and Actinopterygii. Relative gene expression was assessed for each of the analyzed tissues, using the de novo assembled transcriptome and a genome-based analysis using the available T. thymallus genome as a reference. The final assembly, with a contig N50 of 1221 and Benchmarking Universal Single-Copy Orthologs (BUSCO) scores above 94%, is made accessible along with structural and functional annotations and relative gene expression of the five tissues (NCBI SRA and FigShare databases). This is the first transcriptomic resource for this species, which provides a foundation for future research on this and other salmonid species that are increasingly exposed to environmental stressors.

Report on the occurrence of the hydromedusa Odessia maeotica (Ostroumoff, 1896) in the north-eastern Atlantic revealed by citizen science and integrative taxonomy - Rita F. T. Pires; Elsa Froufe; Giulia Secci-Petretto; Antonina dos Santos (Aquatic Ecology, 2024)

An historical “wreck”: A transcriptome assembly of the naval shipworm, Teredo navalis Linnaeus, 1978 - André Gomes-dos-Santos; Marcos Domingues; Raquel Ruivo; Elza Fonseca; Elsa Froufe; Diana Deyanova; João N. Franco; L. Filipe C. Castro (Marine Genomics, 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

The silent extinction of freshwater mussels in Portugal - Manuel Lopes-Lima; Joaquim Reis; Maria G. Alvarez; Pedro M. Anastácio; Filipe Banha; Pedro Beja; Paulo Castro; Mafalda Gama; Maria G. Gil; André Gomes-dos-Santos; Fernando Miranda; Joana Garrido Nogueira; et al. (Biological Conservation, 2023)

First Confirmed Record of the Smalltooth Sand Tiger, Odontapis Ferox, in Galicia (NW Spain) - Gonzalo Mucientes; Nair Vilas-Arrondo; Giulia Secci-Petretto; Uxía Vázquez; Xabier Pin; Alfredo López; L. Filipe C. Castro; Elsa Froufe (Thalassas: An International Journal of Marine Sciences, 2023)
The smalltooth sand tiger shark Odontaspis ferox (Risso, 1810) appears to have an extensive and fragmented distribution in tropical and warm-temperate worldwide oceans. One female of O. ferox was caught and released by a small-scale fishery vessel in Ría de Arousa (Northwest of Spain), subsequently stranded still alive on the coast (42°33’18.4"N 8°49’18.3"O) after a few hours. The individual (336 cm total length, weight ~ 300 kg) was identified based on a collection of features including the characteristic dentition, body morphology and by molecular assignment. This is the first confirmed record of O. ferox in Galician waters. This finding complements the knowledge of the geographic distribution and occurrence of this rare and sparse species in the Northeastern Atlantic.

Joint species distribution models unveil co‐occurrences between freshwater mussels and their fish hosts - Janine P. da Silva; Duarte Vasconcelos Gonçalves; Aina Garcia‐Raventós; Manuel Lopes‐Lima; Simone Varandas; Elsa Froufe; Amílcar Teixeira; Francis K. C. Hui; Ana Filipa Filipe; Ronaldo Sousa (Journal of Biogeography, 2023)
Aim Freshwater mussels are among the most threatened taxa in the world, partially due to the dependence on fish hosts to complete their life cycle. Knowledge about the role of environmental and biotic drivers in determining mussels' distribution is currently lacking. We aimed to assess the role of environmental and biotic drivers in determining the distribution of mussels and their fish hosts and to test if co‐occurrence patterns were able to identify mussel‐host interactions. Location Douro River basin (Iberian Peninsula). Taxon Four freshwater mussels and ten fish hosts. Methods Joint species distribution models (JSDMs) were fitted to presence‐absence records for mussel and fish assemblages. Variance partitioning among environmental variables and latent variables was conducted to determine the environmental versus biotic drivers of species distributions. Resulting matrices of pairwise species co‐occurrences were used to identify co‐occurrence patterns. Results The distribution of host generalist mussel species was mainly explained by environmental variables related to climate and topography. The distribution of the host specialist Margaritifera margaritifera was mainly explained by land use. Strong positive correlations between mussels and the most relevant fish hosts were consistently captured by JSDMs. Co‐occurrence patterns were mainly explained by residual factors, indicating the potential role of biotic interactions. Main Conclusions Biotic interactions were expected to play an important role in explaining mussels' distribution, but the contribution of this factor was only meaningful for the host specialist M. margaritifera . Correlations between mussels and suitable hosts allowed to infer important fish hosts for freshwater mussels in the Douro River basin from distributional data alone. By finding similarities between the ecological requirements of co‐occurring species, conservation measures can be oriented towards several species, which brings a more holistic perspective to the protection of biodiversity.

Identifying freshwater priority areas for cross-taxa interactions - Joana Garrido Nogueira; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe; Elsa Froufe; Duarte V. Gonçalves; Janine P. da Silva; Ronaldo Sousa; Amílcar Teixeira; Simone Varandas; Virgilio Hermoso (Science of The Total Environment, 2023)

Evaluating a species phylogeny using ddRAD SNPs: Cyto-nuclear discordance and introgression in the salmonid genus Thymallus (Salmonidae) - Giulia Secci-Petretto; Gernot K. Englmaier; Steven J. Weiss; Alexander Antonov; Henri Persat; Gael P.J. Denys; Tamara Schenekar; Vladimir I. Romanov; Eric B. Taylor; Elsa Froufe (Molecular Phylogenetics and Evolution, 2023)

Multilocus species delimitation analyses show junior synonyms and deep-sea unknown species of genus Gaidropsarus (Teleostei: Gadiformes) in the North Atlantic/Mediterranean Sea area - David Barros-García; Ángel Sebastián Comesaña; Rafael Bañón; Francisco Baldó; Juan Carlos Arronte; Elsa Froufe; Alejandro De Carlos (Marine Biology, 2022)

Environmental DNA metabarcoding for freshwater bivalves biodiversity assessment: methods and results for the Western Palearctic (European sub-region) - Vincent Prié; Alice Valentini; Manuel Lopes-Lima; Elsa Froufe; Mathieu Rocle; Nicolas Poulet; Pierre Taberlet; Tony Dejean (Hydrobiologia, 2021)

Phylogeographic study of the West Australian freshwater mussel, Westralunio carteri, uncovers evolutionarily significant units that raise new conservation concerns - M. W. Klunzinger; Manuel Lopes-Lima; Andre Gomes-dos-Santos; Elsa Froufe; A. J. Lymbery; L. Kirkendale (Hydrobiologia, 2021)

Global systematic diversity, range distributions, conservation and taxonomic assessments of graylings (Teleostei: Salmonidae; Thymallus spp.) - Steven J. Weiss; Duarte V. Gonçalves; Giulia Secci-Petretto; Gernot K. Englmaier; André Gomes-Dos-Santos; Gael P. J. Denys; Henri Persat; Alexander Antonov; Christoph Hahn; Eric B. Taylor; Elsa Froufe (Organisms Diversity & Evolution, 2021)
Graylings ( Thymallus ) are among the less well-studied groups of salmonid fishes, especially across their Asian distribution range. Here we perform a comprehensive global review of their phylogeography, systematic diversity and range distributions, including biogeographic reconstruction and assessment of both conservation and taxonomic status of each species. Based on a mitogenomic phylogenetic analysis, three approaches to the delineation of molecular operational units, and evaluation of 15 a-priori defined species, we provide biological support for the recognition of 13 grayling species, plus two additional species tentatively. Several instances of paraphyly and its potential effect on systematic inferences are discussed. Overall, the genus displays increasing species diversity and decreasing range size from higher to lower latitudes and ancestral trait reconstruction supports an East Asian origin for extant diversity, most likely centred in the Amur River drainage. Europe’s colonization by Thymallus took place as early as the late Miocene, at least two colonisations of North America are supported, and multiple dispersal events likely took place into Western Siberia. The conservation status for the 15 taxa was estimated to be: 6 least concern, 1 near-threatened, 2 vulnerable, 3 endangered and 3 data deficient.

Publisher Correction to: Comparative genetic analysis of grayling (Thymallus spp. Salmonidae) across the paleohydrologically dynamic river drainages of the Altai-Sayan mountain region - Steven Weiss; Jacqueline Grimm; Duarte V. Gonçalves; Giulia Secci-Petretto; Gernot K. Englmaier; Mirgaliy Baimukanov; Elsa Froufe (Hydrobiologia, 2020)

Origin and history of Phoxinus (Cyprinidae) introductions in the Douro Basin (Iberian Peninsula): an update inferred from genetic data - Aina Garcia-Raventós; Filipa M. S. Martins; Amilcar Teixeira; Ronaldo Sousa; Elsa Froufe; Simone Varandas; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe (Biological Invasions, 2020)

Comparative genetic analysis of grayling (Thymallus spp. Salmonidae) across the paleohydrologically dynamic river drainages of the Altai-Sayan mountain region - Steven Weiss; Jacqueline Grimm; Duarte V. Gonçalves; Giulia Secci-Petretto; Gernot K. Englmaier; Mirgaliy Baimukanov; Elsa Froufe (Hydrobiologia, 2020)
A high number of grayling ( Thymallus ) species have been described from the Altai-Sayan mountain region, for which little to no genetic information is available. We investigated genetic relationships within this genus of salmonid fishes using mtDNA and microsatellite markers. The analysis focused on three putative species, Markakol grayling ( T. brevicephalus ), Upper Ob grayling ( T. nikolskyi ) and Mongolian grayling ( T. brevirostris ). We integrated these data with mtDNA sequences from eight other grayling species, including two of geographic proximity to the study area. Phylogenetic results revealed three pairs of reciprocally monophyletic sister species, two of which were phylogenetically juxtaposed across isolated drainage systems. Based on microsatellite analysis (up to 10 loci) no evidence of hybridization or introgression was found among species, supporting the mtDNA phylogeny. Based on a time-calibrated tree, divergence times between the focal taxa ranged from 0.36 to 1.1 MY. The genetic data support the distinction of these species and underscore the importance of paleohydrological dynamics in this biogeographically complex region. Well-documented mega-flood events in the region provide a model of how the contemporary cross-basin distribution of these species may have evolved.

Molluscan genomics: the road so far and the way forward - André Gomes-dos-Santos; Manuel Lopes-Lima; L. Filipe C. Castro; Elsa Froufe (Hydrobiologia, 2020)

Multiple species of grayling ( Thymallus sp.) found in sympatry in a remote tributary of the Amur River - Steven Weiss; Giulia Secci‐Petretto; Alexander Antonov; Elsa Froufe (Zoologica Scripta, 2020)
Large‐scale phenotypic and genetic studies of the salmonid genus Thymallus (grayling) in the Palaearctic suggest that most major phylogeographic lineages represent good biological species. Evaluating such a premise in areas involved in palaeo‐hydrological dynamics where multiple species are found in sympatry should serve to assess the level of reproductive isolation, the traditional sine qua non of species recognition. Molecular sequence (mtDNA) and microsatellite (nDNA, seven loci) analysis of grayling in the upper Bureya River watershed support the occurrence of three distinctive species of grayling living in sympatry in this large oligotrophic tributary of the Amur River. One of these lineages is primarily found throughout the Lena River basin and is recognized as Baikal‐Lena grayling Thymallus baicalolenensis ; the second, the upper Amur grayling Thymallus grubii is found over large areas of the Amur catchment including the entire headwater region; and the third, the Bureya grayling Thymallus burejensis is endemic to the study area. A limited number of hybrids were identified, primarily between Baikal‐Lena grayling T. baicalolenensis and Bureya grayling T. burejensis with little to no signs of introgression among non‐hybrid individuals. Morphological distinctiveness among populations of these species living in sympatry was greater than between populations living in allopatry, suggesting character displacement. Divergence estimates among taxa range up to 6.2 MY, and allopatric origins for all three species’ is suggested. To our knowledge, this is the first data‐based confirmation of three species of grayling living in sympatry.

Revisiting the North American freshwater mussel genus Quadrula sensu lato (Bivalvia Unionidae): Phylogeny, taxonomy and species delineation - Manuel Lopes‐Lima; Lyubov Burlakova; Alexander Karatayev; André Gomes‐dos‐Santos; Alexandra Zieritz; Elsa Froufe; Arthur E. Bogan (Zoologica Scripta, 2019)
Freshwater mussels (Bivalvia, Unionidae) have suffered strong declines over the last century. High morphological plasticity of Unionidae causes disturbances in their systematics and taxonomy, hampering conservation efforts. Species that have historically been placed under the North American genus Quadrula have suffered from numerous taxonomic and species delineation problems since its inception. Four genera are presently recognized within Quadrula sensu lato, that is, Cyclonaias , Quadrula , Theliderma and Tritogonia , but their phylogenetic basis remains incompletely tested. In the present study, we reconstructed several two‐marker (mtDNA cytochrome c oxidase subunit I—COI and NADH dehydrogenase subunit 1—ND1) phylogenies with newly collected specimens and all previously available sequences covering most species within this group. We then delineated the species within the group using an integrative approach with the application of molecular statistical methods, morphometric (Fourier Shape) analyses and geographic distribution data. Four clades corresponding to these genera were consistently recovered in all phylogenies. To validate the generic status of these clades, molecular analyses were complemented with morphological, anatomical and ecological data compiled from the literature. Several revisions are here proposed to the current systematics and taxonomy of these genera, including the synonymization of Cyclonaias asperata under Cyclonaias kieneriana ; the inclusion of Quadrula apiculata and Quadrula rumphiana under Quadrula quadrula ; the placement of Quadrula nobilis under Tritogonia ; and finally the separation of the Mobile River basin populations of Theliderma metanevra as a new species, that is, Theliderma johnsoni n. sp. The conservation implications of the proposed changes are then discussed.

Genetic diversity and population structure of the blue jack mackerel Trachurus picturatus across its western distribution - Cláudia Moreira; Alberto T. Correia; Paulo Vaz‐Pires; Elsa Froufe (Journal of Fish Biology, 2019)
Blue jack mackerel Trachurus picturatus collected at six sampling locations of the north‐east Atlantic Ocean (Azores, Madeira, Canaries, and Matosinhos, Peniche and Portimão, mainland Portugal) and one location in the Mediterranean (Sicily), were used to examine the genetic structure of this species. Three mitochondrial gene regions (cytochrome c oxidase subunit I, cytochrome b and control region) were used to study the genetic structure of the species in Macaronesia, as well as to compare the genetic diversity of this region with published results from its eastern distribution. All markers indicated the absence of genetic structure among populations, with high indices of genetic diversity. These results suggest that the species went through a bottleneck event, followed by a recent population expansion. Moreover, the comparison with previously published results from the T. picturatus Mediterranean distribution suggests the existence of a single panmictic population throughout the species' full range. This was, however, an unexpected result since other methodologies have shown the presence of, at least, three different population‐units in the NE Atlantic Ocean.

Phylogeography of the deep-sea morid codling Lepidion lepidion reveals the presence of two ancient atlantic/mediterranean lineages. - David Barros-García; Elsa Froufe; Rafael Bañón; Juan Arronte; Francisco Baldó; Alejandro De Carlos (Frontiers in Marine Science, 2019)

Stock structure of Trachurus picturatus from the NE Atlantic and Mediterranean Sea using microsatellite DNA markers - Cláudia Moreira; PabloPablo Presa; Alberto Correia; Paulo Vaz-Pires; Elsa Froufe (Frontiers in Marine Science, 2019)

Current state of research on the systematics and zoogeography of graylings (Thymallus) throughout the world, with notes on the recent advances and applications of genomics. - Steven Weiss; Gernot Englmaier; Giulia Secci-Petretto; Elsa Froufe (Frontiers in Marine Science, 2019)

Unravelling the population structure of Trachurus picturatus across the NE Atlantic using otolith fingerprinting analyses - Cláudia Moreira; Elsa Froufe; Paulo Vaz-Pires; Raül Triay-Portella; Jorge Castro; Alberto Correia (Frontiers in Marine Science, 2019)

Population structure, habitat connectivity and movement patterns of the blue jack mackerel, Trachurus picturatus, in the NE Atlantic: combining natural tags for a rational management of fisheries resources - Cláudia Moreira; Elsa Froufe; Paulo Vaz-Pires; Pablo Presa; Raül Triay-Portella; Alberto Correia (Frontiers in Marine Science, 2019)

Mitogenome Phylogeny of Thymallus (graylings) - Species delineation - Giulia Secci-Petretto; Steven Weiss Weiss; André Gomes-dos-Santos; Henri Persat; Gaël Denys; Elsa Froufe (Frontiers in Marine Science, 2019)

Does Loire grayling represent a distinct species ? - Henri PERSAT; Gaël Denys; Elsa Froufe; Giulia Secci-Petretto; Steven Weiss Weiss (Frontiers in Marine Science, 2019)

Unravelling the systematics of Nodularia (Bivalvia, Unionidae) species from eastern Russia - Olga K. Klishko; Manuel Lopes-Lima; Elsa Froufe; Arthur E. Bogan; Vera Y. Abakumova (Systematics and Biodiversity, 2018)

Diversity, biogeography and conservation of freshwater mussels (Bivalvia: Unionida) in East and Southeast Asia - Alexandra Zieritz; Arthur E. Bogan; Elsa Froufe; Olga Klishko; Takaki Kondo; Uthaiwan Kovitvadhi; Satit Kovitvadhi; Jin Hee Lee; Manuel Lopes-Lima; John M. Pfeiffer; Ronaldo Sousa; Tu Van Do; et al. (Hydrobiologia, 2018)

Lifting the curtain on the freshwater mussel diversity of the Italian Peninsula and Croatian Adriatic coast - Elsa Froufe; Manuel Lopes-Lima; Nicoletta Riccardi; Serena Zaccara; Isabella Vanetti; Jasna Lajtner; Amílcar Teixeira; Simone Varandas; Vincent Prié; Alexandra Zieritz; Ronaldo Sousa; Arthur E. Bogan (Biodiversity and Conservation, 2017)

Who lives where? Molecular and morphometric analyses clarify which Unio species (Unionida, Mollusca) inhabit the southwestern Palearctic - Elsa Froufe; Duarte V. Gonçalves; Amílcar Teixeira; Ronaldo Sousa; Simone Varandas; Mohamed Ghamizi; Alexandra Zieritz; Manuel Lopes-Lima (Organisms Diversity & Evolution, 2016)

Population structure of the blue jack mackerel (Trachurus picturatus) in the NE Atlantic inferred from otolith fingerprinting - Moreira Cláudia; Froufe Elsa; Correia Alberto (Frontiers in Marine Science, 2016)

Phylogeography of the species Trachurus picturatus (Bowdich 1825) inferred from mitochondrial and nuclear DNA sequence data - Moreira Cláudia; Correia Alberto; Froufe Elsa (Frontiers in Marine Science, 2016)

First record of the freshwater jellyfish Craspedacusta sowerbii Lankester, 1880 in Greece suggests distinct European invasion events - Ioannis Karaouzas; Stamatis Zogaris; Manuel Lopes-Lima; Elsa Froufe; Simone Varandas; Amílcar Teixeira; Ronaldo Sousa (Limnology, 2015)

New insights about the population structure of the blue jack mackerel (Trachurus picturatus) in the NE Atlantic using otolith stable isotope ratios - Moreira Cláudia; Froufe Elsa; Caeiro Alberto; Sial Alcides; Correia Alberto (Frontiers in Marine Science, 2015)

Preliminary data on Trachurus picturatus (Bowdich 1825) phylogeography inferred from mitochondrial DNA sequence data - Moreira Cláudia; Correia Alberto; Caeiro Alberto; Froufe Elsa (Frontiers in Marine Science, 2015)

Biology and conservation of freshwater bivalves: past, present and future perspectives - Manuel Lopes-Lima; Amílcar Teixeira; Elsa Froufe; Anabela Lopes; Simone Varandas; Ronaldo Sousa (Hydrobiologia, 2014)

The environmental impact of Lagrangian transport routes in the north east atlantic ocean. - Sala Iria; Caldeira Rui; Estrada-Allis Sheila; Froufe Elsa; Couvelard Xavier (Frontiers in Marine Science, 2014)

Ecological Status of a Margaritifera margaritifera (Linnaeus, 1758) Population at the Southern Edge of its Distribution (River Paiva, Portugal) - Ronaldo Sousa; Ângela Amorim; Carina Sobral; Elsa Froufe; Simone Varandas; Amílcar Teixeira; Manuel Lopes-Lima (Environmental Management, 2013)

Integrating molecular ecology and predictive modelling: implications for the conservation of the barbastelle bat (Barbastella barbastellus) in Portugal - Hugo Rebelo; Elsa Froufe; Nuno Ferrand; Gareth Jones (European Journal of Wildlife Research, 2012)

Postglacial colonization of Europe by the barbastelle bat: agreement between molecular data and past predictive modelling - HUGO REBELO; ELSA FROUFE; JOSÉ C. BRITO; DANILO RUSSO; LUCA CISTRONE; NUNO FERRAND; GARETH JONES (Molecular Ecology, 2012)
The barbastelle ( Barbastella barbastellus ) is a rare forest bat with a wide distribution in Europe. Here, we combine results from the analysis of two mtDNA fragments with species distribution modelling to determine glacial refugia and postglacial colonization routes. We also investigated whether niche conservatism occurs in this species. Glacial refugia were identified in the three southern European peninsulas: Iberia, Italy and the Balkans. These latter two refugia played a major role in the postglacial colonization process, with their populations expanding to England and central Europe, respectively. Palaeo‐distribution models predicted that suitable climatic conditions existed in the inferred refugia during the last glacial maximum (LGM). Nevertheless, the overlap between the current and the LGM distributions was almost inexistent in Italy and in the Balkans, meaning that B. barbastellus populations were forced to shift range between glacial and interglacial periods, a process that probably caused some local extinctions. In contrast, Iberian populations showed a ‘refugia within refugium’ pattern, with two unconnected areas containing stable populations (populations that subsisted during both glacial and interglacial phases). Moreover, the match between LGM models and the refugial areas determined by molecular analysis supported the hypothesis of niche conservatism in B. barbastellus . We argue that geographic patterns of genetic structuring, altogether with the modelling results, indicate the existence of four management units for conservation: Morocco, Iberia, Italy and UK, and Balkans and central Europe. In addition, all countries sampled possessed unique gene pools, thus stressing the need for the conservation of local populations.

Phylogeographical history of the white seabream Diplodus sargus (Sparidae): Implications for insularity - Mercedes González-Wangüemert; Elsa Froufe; Angel Pérez-Ruzafa; Paulo Alexandrino (Marine Biology Research, 2011)

Genetic diversity within Scorpio maurus (Scorpiones: Scorpionidae) from morocco: Preliminary evidence based on CO1 mitochondrial DNA sequences - Elsa Froufe; Pedro Sousa; Paulo C. Alves; David J. Harris (Biologia, 2008)

Mitochondrial Gene Rearrangements and Partial Genome Duplications Detected by Multigene Asymmetric Compositional Bias Analysis - Miguel M. Fonseca; Elsa Froufe; D. James Harris (Journal of Molecular Evolution, 2006)